Trefoil factor peptides in serum and sputum from subjects with asthma and COPD. (16th June 2014) - Viby, Niels‐Erik; Pedersen, Lars; Lund, Thomas Kromann; Kissow, Hannelouise; Backer, Vibeke; Nexø, Ebba; Thim, Lars; Poulsen, Steen Seier
Abstract Objective Trefoil factor peptides (TFF) are secreted onto mucosal surfaces together with mucins and occur in high concentrations in pulmonary secretions from patients with chronic obstructive pulmonary disease (COPD). In the present study, we aimed to explore the concentrations of the peptides in serum and sputum in patients with COPD. Materials and Methods Thirty‐five individuals were included in the study, including 11 healthy individuals, 13 indivials with asthma and 11 individuals with COPD. TFF1, TFF2 and TFF3 were measured by enzyme‐linked immunosorbent assay (ELISA) in sputum induced by hypertonic saline inhalation and in serum. Total protein content in sputum was also determined. Results In the sputum samples from COPD patients, we observed an eightfold higher concentration of TFF1 and a fivefold higher concentration of TFF3 compared with controls. In the serum samples from COPD patients, we observed three‐, three‐ and twofold higher concentrations of TFF1, TFF2 and TFF3 respectively compared with controls. Conclusions There is increased secretion of TFF peptides in the lungs of patients with COPD, as well as significant increases in serum levels. This suggests a role for TFF peptides in the pathogenesis of pulmonary diseases with mucus hypersecretion.